Factors associated with symptom burden in adults with chronic kidney disease undergoing hemodialysis: a prospective study - Gunarathne, Thalwaththe Gedara Nadeeka Shayamalie; Tang, Li Yoong; Lim, Soo Kun; Nanayakkara, Nishantha; Damayanth, Hewaratne Dassanayakege Wimala Thushari; Khatijah Lim, Abdullah * (MDPI, 2022)
People with end stage renal disease and undergoing hemodialysis experience a high symptom burden that impairs quality of life. This study aimed to assess the prevalence, dynamicity and determinants of symptom burden among middle-aged and older adult hemodialysis patients. A descriptive cross-sectional study together with a longitudinal assessment was used. A total of 118 and 102 hemodialysis patients were assessed at baseline and at a 6-month follow-up. Validated questionnaires were used to assess the symptom burden, stress, illness perception and social support. Multiple linear regression analysis was used to determine the factors associated with symptom burden. The median number of symptoms experienced was 21 (Interquartile Range (IQR); 18−23) and 19 (IQR; 13−22) at baseline and 6 months, respectively. Having elevated stress (β = 0.65, p ≤ 0.005) and illness perception (β = 0.21, p = 0.02) were significantly predicted symptom burden at baseline (F (4, 112) = 55.29, p < 0.005, R2 = 0.664). Stress (β = 0.28, p = 0.003), illness perception (β = 0.2, p = 0.03), poor social support (β = −0.22, p = 0.01) and low body weight (β = −0.19, p = 0.03) were the determinants for symptom burden at 6 months (F (5, 93) = 4.85, p ≤ 0.005, R2 = 0.24). Elevated stress, illness perception level, poor social support and low post-dialysis body weight were found to be determinants for symptom burden. Attention should be given to psychosocial factors of hemodialysis patients while conducting assessment and delivering care to patients.